Thúc đẩy tham gia bảo hiểm xã hội cho doanh nghiệp tại Vĩnh Long: Mối quan hệ với các bên liên quan và ứng dụng VSSID - Nguyen Hoang, Long; Tran Thi Hong, Cuc; Doan Thi Thanh, Hoa; Nguyen Thi, Diem (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study analyzes factors influencing the non-participation in social insurance (SI) by enterprises in Vinh Long province. Data from 316 non-participating enterprises, analyzed using the PLS-SEM model and FsQCA method, reveal that poor awareness among business owners, lenient enforcement, low non-compliance risk, and information asymmetry significantly contribute to non-compliance. The study also finds that stakeholder relationships and the use of the VssID application help mitigate these barriers. However, even with strong stakeholder relationships, enterprises may still choose not to participate in SI if they perceive low violation risks and possess significant information advantages. Similarly, using VssID does not guarantee compliance if SI awareness and stakeholder relationships are weak. Based on these findings, the study suggests policy implications for SI authorities to encourage enterprise participation in the future.